Additive manufacturing SWOT analysis for metallic applications - Lee, Kimberly Ruo Qing (2017)
Since the development of rapid prototyping in the late 1980s, the manufacturing industry has seen the growth in manufacturing technologies using Computer Aided Design Software (CAD) and Computer Aided Manufacturing Software (CAM). In the last three decades, such machines and technologies have progressed from being limited to prototyping to being able to manufacture products in large quantities. The ability to create designs in software and to build 3D products layer by layer in an additive manner has allowed for design flexibility and presents new capabilities for not just the manufacturers but also other industries. This technology that has gained worldwide attention and had created a technological research hype is known as – Additive Manufacturing.